2014
DOI: 10.1186/1750-1172-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of females with HCCS mutation: from no clinical signs to a neonatal lethal form of the microphthalmia with linear skin defects (MLS) syndrome

Abstract: BackgroundSegmental Xp22.2 monosomy or a heterozygous HCCS mutation is associated with the microphthalmia with linear skin defects (MLS) or MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome, an X-linked disorder with male lethality. HCCS encodes the holocytochrome c-type synthase involved in mitochondrial oxidative phosphorylation (OXPHOS) and programmed cell death.MethodsWe characterized the X-chromosomal abnormality encompassing HCCS or an intragenic mutation in this gene in six new female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Wimplinger et al 2006 reported a female, born to healthy nonconsanguineous parents after an uneventful pregnancy, found to have bilateral microphthalmia and sclerocornea but no erythematous skin lesions. She had a de novo HCCS nonsense variant (c.589C > T; p.(R197*)) that was also reported in an additional case with both MLS and histiocytoid CM (van Rahden et al 2014). Around 1 yr of age she was reported to have developed “idiopathic VT” (Wimplinger et al 2006).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Wimplinger et al 2006 reported a female, born to healthy nonconsanguineous parents after an uneventful pregnancy, found to have bilateral microphthalmia and sclerocornea but no erythematous skin lesions. She had a de novo HCCS nonsense variant (c.589C > T; p.(R197*)) that was also reported in an additional case with both MLS and histiocytoid CM (van Rahden et al 2014). Around 1 yr of age she was reported to have developed “idiopathic VT” (Wimplinger et al 2006).…”
Section: Discussionmentioning
confidence: 56%
“…We hypothesize that HCCS (OMIM 30056) and COX7B (OMIM 300885) , which are X-linked genes encoding or targeting mitochondrial proteins and are implicated in MLS, are good candidate genes for histiocytoid CM. We note that van Rahden et al (2014) have reported previously a female child with a de novo HCCS nonsense variant (c.589C > T; p.(R197*)) and extremely skewed X-inactivation (98:2) with classical features of MLS including linear skin defects on her neck, microphthalmia, anophthalmia, and sclerocornea, who died at 4 mo with ventricular tachycardia (VT) and was found to have histiocytoid CM on postmortem examination, further supporting that MLS and histiocytoid CM are allelic disorders. However, no rare variants were found in HCCS or COX7B in seven additional histiocytoid CM cases without NDUFB11 variants (four described here, three in Shehata et al 2015), though this small series does not exclude a role in “isolated” histiocytoid CM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The diagnosis is supported by minor criteria (Table ) and/or a family history consistent with X‐linked inheritance with male lethality. It has been hypothesized that the particular involvement of neural crest cells explains the linear skin defects restricted to the face and neck . The defects demonstrate dermoscopic features of telangiectasias and absence of sebaceous glands and vellus hair .…”
Section: Criteria For Microphthalmia With Linear Skin Defectsmentioning
confidence: 99%
“…MLS syndrome is genetically heterogenous, with heterozygous mutations in the gene for human holocytochrome c synthase ( HCCS ) having been identified in MLS‐affected females . In total, 62 cases of MLS syndrome have been reported, of which 11 cases were familial . We present a further case of familial MLS.…”
mentioning
confidence: 99%